Vem läser en dialektordbok? - Vem skriver vi för? - Eaker, Birgit (Nordiske Studier i Leksikografi, 1997)
That writers of dialect dictionaries have had different categories of readers in mind is apparent from their prefaces, their choice of given information and their presentation of it. This is illustrated by examples from different dialect dictionaries, both regional and local, as well as from the two earlier dictionaries covering all of Sweden by J. Ihre and J. E. Rietz, respectively. The new Swedish Dialect Dictionary undertakes to present all the Swedish dialects in present-day Sweden to schalars as well as to interested laymen. Our approach to this task is ill ustrated by an article from the dictionary. F inally, same changes in progress are presented. These focus on making the dictionary easier to use, especially for the layman. They also include providing some encyclopedical data for the better understanding of words denoting objects, processes, etc., from a rural environment little known to the reader oftoday or ofthe future.